Novel CO2-tolerant Co-based double perovskite cathode for intermediate temperature solid oxide fuel cells. Issue 3 (March 2023) - Liu, Yaowei; Cao, Yuchen; Sun, Shisheng; Lu, Chunling; Wang, Biao; Liu, Gaobin; Gao, Shoushan; Niu, Bingbing
Abstract: For the commercial application of solid oxide fuel cells (SOFCs), CO2 -tolerant cathode materials with high electrochemical activity are required. Here, we discuss the performance of double perovskite Pr0.2 Sr1.8 CoTiO6−δ (P02STC) as a potential cathode material for SOFCs. P02STC has a cubic structure and keeps lattice structure stable in the CO2 atmosphere. The average thermal expansion coefficient is 17.8 × 10 –6 K –1 at 30–900 °C in air. The P02STC cathode exhibits good electrochemical performance with a low polarization resistance of 0.080 Ωcm 2 at 700 °C. The P02STC cathode shows good structure stability, electrochemical performance stability, and excellent tolerance to CO2 poisoning for the symmetrical cells based on the 350 h stability test in air and the 150 h stability test in O2 containing 5%CO2 at 700 °C. The electrolyte-supported single cell with a P02STC cathode shows a maximum power density of 677 mW cm − 2 at 800 °C. The single cell operates stably for 250 h at a constant current of 0.3 A/cm 2 without obvious degrading performance. According to all of the experimental results, the P02STC sample might be a promising candidate cathode for SOFCs. Highlights: Pr0.2 Sr1.8 TiCoO6-δ (P02STC) has good structural stability in air and pure CO2 . Electrochemical stability test demonstrates the satisfied structure stability and CO2 -resistance ability of P02STC. P02STC as cathode for SOFC exhibits good electrochemical performance and stability.